Study on the installation of harmonic filter circuits for industrial plants connected to solar energy systems and low harmonic currents - C. Boonseng; Poomipat Gitnumlapcharoen; R. Boonseng (My University, 2023)
In industrial systems, solar power systems are used to reduce environmental impact and use less energy from the grid. Solar energy systems have non-linear electrical characteristics that cause harmonic problems. Such problems result in damage to electrical equipment despite the small amount of harmonic current. This paper presents a suitable and simple analytical method to solve this problem by installing a passive filter.
Keywords: Smart Grid and Power Systems; High-Voltage Power Transmission Systems; Power Systems and Renewable Energy